-10(109)+80x=5(x-8)

Simple and best practice solution for -10(109)+80x=5(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(109)+80x=5(x-8) equation:



-10(109)+80x=5(x-8)
We move all terms to the left:
-10(109)+80x-(5(x-8))=0
We calculate terms in parentheses: -(5(x-8)), so:
5(x-8)
We multiply parentheses
5x-40
Back to the equation:
-(5x-40)
We get rid of parentheses
80x-5x+40-10109=0
We add all the numbers together, and all the variables
75x-10069=0
We move all terms containing x to the left, all other terms to the right
75x=10069
x=10069/75
x=134+19/75

See similar equations:

| 2(t-3)+2=2(2t-7) | | 2x+5 + x = 29 | | -3x+52+7x=105+27-x | | 19(x+5)=2(x+9)+230 | | 7x+6=x+54 | | 2m^2=5m-5 | | 8-6=22x | | -0.10(17)+0.45x=0.05(x-2) | | 3=y/2-5 | | 0.10(-37)+0.60x=0.05(30-x) | | 3x-38=0 | | 6y^2+9y-86=0 | | 3x-9+11-4x=6x-8 | | 100x2-140x+49=0 | | Y=-16T^2+85t+120 | | 2x-8x+3=x-3+6 | | 3(x+4)+4=3x+7 | | -0.10(12)+0.30x=0.05(x-14) | | 3*(5t+1)=t+4+t-2 | | 12x+15–6x=43 | | 3*5t+1=t+4+t-2 | | 23y=67 | | X-(3x+2)=-2-x | | 18r+15=69-9r | | 2-(3x-21)=5(x-2) | | 2x+1/18=1/2 | | 158-10k=7k+5 | | 16v+3=88-v | | 397-9x=18x+19 | | 168-17v=-9v+16 | | -211-5x=-19x+13 | | 15r-4=6r+32 |

Equations solver categories